An updated review of the salient geomedical aspects of mercury for enhancement of data quality in simulation modelling and other prognostic applications: Africa case descriptions - Davies, Theophilus C. (Frontiers in Analytical Science, 2023)
Mercury (Hg) pollution is of global concern. Despite the prolificity of research in the past two decades or so, there are still several uncertainties and variabilities in our knowledge of both the element’s exposure dynamics and its health effects. Understanding the intricacies of the element’s emissions-to-impact path, for instance, is rendered intractable by its varied environmental fate and the overarching influence of environmental, geochemical, biological and socioeconomic drivers. In this paper, an updated synopsis of the relevant and more important geomedical characteristics of Hg is considered to constitute part of the provision of high-quality input data needed in Hg simulation modelling studies, and other applications such as the provision of long-term data necessary for evaluating the effectiveness of regulatory measures at various scales. A critical overview is presented on the importance of data quality in parameterisation, and validation of Hg simulation models and other related applications. In this connection, the dearth of modern measurements of Hg abundance in crustal rocks and other Earth materials which needs to be set prior to simulation as well as in modelling source to sink transfers in the Hg cycle, is highlighted. An improved input data quality would also foster the production of model outcomes that are accurate enough for applications in design of better exposure-limiting strategies; and in providing insights on how the course of diagnosis and treatment currently proffered by physicians for Hg-induced maladies, can be revised or expanded. Model results derived from high-quality input datasets also have a high potential for providing forecasting capabilities to inform policy.